Developing a Community-Based Non-Structural Disaster Mitigation Module Integrating Local Knowledge: Evidence from Indonesia as a Middle-Income Country - Suparji Suparji; Heru Santoso Wahito Nugroho; Sunarto Sunarto; Alfi Rusdianti (Knowledge Dynamics, 2026)
Background: Natural disasters continue to pose significant challenges globally, particularly in disaster-prone middle-income countries such as Indonesia, where communities are frequently exposed to hydrometeorological and geological hazards. While structural mitigation remains important, non-structural and community-based approaches are increasingly emphasized to enhance contextual relevance and community engagement in disaster risk reduction. This study aimed to develop and assess the feasibility of a community-based non-structural disaster mitigation module integrating local knowledge as an educational resource for disaster-prone communities. Methods: The study employed a Research and Development (R&D) approach using a simplified adaptation of the Borg and Gall model. The development process included a needs assessment through in-depth interviews and focus group discussions, module design and development, expert validation, and a limited field trial with target community users. Data were collected using qualitative methods and structured questionnaires, and analyzed descriptively to examine feasibility, acceptability, and relevance. Results: The results indicate that the developed module achieved high feasibility scores across content, presentation, language, and integration of local knowledge. User assessments from the limited field trial demonstrated high levels of acceptability and relevance, particularly in relation to clarity, contextual suitability, and usefulness as a learning resource. Revisions based on expert and user feedback were incorporated into the final version of the module. Conclusions: In conclusion, this study provides early empirical evidence supporting the feasibility and acceptability of a community-based non-structural disaster mitigation module that integrates local knowledge. The module shows potential for use as an educational tool to support community disaster preparedness activities within similar middle-income country contexts.